B D Chaurasia's human anatomy ; regional and applied dissection and clinical vlume 2 lower limb,abdomen & pelvis (New Delhi, CBS Publishers & Distribtors, 2004)
Volume 2 available
1 Volume
Keywords: Human anatomy; Leg; Pelvis